Theoretical Design of Generating Tooth Modification Profile with Rack Tools - Feng Jinping; Zhou Guopeng; Lan Gongpu (Jixie chuandong)
Before processing tooth modification profile using NC machine, it is usually necessary to process a specific trimming tool, which increases the cost of the tool. Thus, the theory of how to generate modification profile of tooth based on standard rack tools is studied. Based on the tooth profile modification equation and tooth contact analysis theory, the transmission error equations between rack cutters and gears in the modification process, involute meshing stage and transition stage of empty meshing are deduced, and the position and speed control equations of rack cutters in the NC machining process are given. The simulated tooth profile parameters coincide highly with the ideal design value of tooth profile. The tooth profile modification method proposed can effectively guide the NC machined gear tooth modification profile with the rack tool.